2017
DOI: 10.1038/s41467-017-01917-2
|View full text |Cite
|
Sign up to set email alerts
|

Remodelling of the gut microbiota by hyperactive NLRP3 induces regulatory T cells to maintain homeostasis

Abstract: Inflammasomes are involved in gut homeostasis and inflammatory pathologies, but the role of NLRP3 inflammasome in these processes is not well understood. Cryopyrin-associated periodic syndrome (CAPS) patients with NLRP3 mutations have autoinflammation in skin, joints, and eyes, but not in the intestine. Here we show that the intestines of CAPS model mice carrying an Nlrp3 R258W mutation maintain homeostasis in the gut. Additionally, such mice are strongly resistant to experimental colitis and colorectal cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(138 citation statements)
references
References 69 publications
8
126
0
4
Order By: Relevance
“…Another possible explanation is based on the presence or absence of an environmental factor, such as a microbiome-related development of suppressor cells, that prevents the development of GI disease. This possibility is supported by the recent finding already mentioned above (26), showing that, in mice, a CAPS-like mutation in NLRP3 leading to increased NLRP3 inflammasome activity results in the appearance of a gut organism capable of inducing the development of suppressor T cells. Further work will be necessary to establish these or other explanations of intestinal inflammation in the face of NLRP3 overactivity.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Another possible explanation is based on the presence or absence of an environmental factor, such as a microbiome-related development of suppressor cells, that prevents the development of GI disease. This possibility is supported by the recent finding already mentioned above (26), showing that, in mice, a CAPS-like mutation in NLRP3 leading to increased NLRP3 inflammasome activity results in the appearance of a gut organism capable of inducing the development of suppressor T cells. Further work will be necessary to establish these or other explanations of intestinal inflammation in the face of NLRP3 overactivity.…”
Section: Discussionsupporting
confidence: 69%
“…Thus, in a study by Yao et al, it was shown that mice bearing a mutation in the NLRP3 gene resulting in NLRP3 with increased function similar to that occurring in the autoinflammatory Muckle-Wells syndrome were resistant to DSS-colitis. This was due to IL-1β induction of antibacterial peptides promoting the development of an intestinal microflora containing an organism (Larus marinus) that induces regulatory T cells in the mucosa capable of suppressing inflammation (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies fail to show a specific role for epithelial cells, despite these being the main cell type affected by IBD. In fact, recent studies suggest that NLRP3 is not expressed by epithelial cells in the colon of mice, placing tissue‐resident macrophages as the principal contributors to this NLRP3‐dependent response . These studies suggest that although NLRP3 is a main actor in IBD, the epithelial cell layer's contribution to IBD might be NLRP3 independent.…”
Section: The Inflammasome: a Well‐regulated Immune Platform Also Presmentioning
confidence: 94%
“…In fact, recent studies suggest that NLRP3 is not expressed by epithelial cells in the colon of mice, placing tissue-resident macrophages as the principal contributors to this NLRP3-dependent response. 71 These studies suggest that although NLRP3 is a main actor in IBD, the epithelial cell layer's contribution to IBD might be NLRP3 independent. Surprisingly, epithelial cell-specific depletion of capase-1 induces decreased IL-18 levels and decreased pathology in a DSS-induced colitis model, pointing to the involvement of another inflammasome-forming receptor.…”
Section: Gut Epithelial Cellsmentioning
confidence: 97%
“…Consistent with its role in promoting antitumorigenic interferon-c production, Th1 cell, NK and cytotoxic Tcell (CD8 + T cells) responses [105,115,116], mice lacking IL-18 or its cognate receptor were reported to be hypersusceptible to colitisassociated tumorigenesis in the murine azoxymethane (AOM)/ dextran sodium sulphate (DSS) model of inflammation-associated colorectal cancer [117]. Consistently, other studies showed that AOM/DSS-treated NLRP3 À/À , Nlrp3 R258W , ASC À/À and caspase-1 À/À mice had an increased tumour burden [118][119][120]. Conversely, another study [121] failed to observe changes in colorectal cancer development in AOM/DSS-treated NLRP3 À/À mice, arguing against a tumour-suppressive role for IL-18.…”
Section: Pro-tumorigenic Role Of Il-18 In Solid Tumoursmentioning
confidence: 71%